Baby Bonus, Fertility, and Missing Women - Wookun Kim (CESifo GmbH, 2024)
This paper presents novel causal evidence on the effects of pro-natalist cash transfers on fertility, sex ratio at birth, and infant health. In the context of South Korea, I exploit rich spatial and temporal variation in cash transfers provided to families with newborn babies and the universe of birth-, death-, and migrant-registry records. I find that the total fertility rate in 2015 would have been 4.7% lower without the cash transfers. Surprisingly, the cash transfers had an unintended consequence of correcting the unnaturally male-skewed sex ratio at birth. The cash transfers led to reductions in gestational age and birth weight, but no change in early-life mortality. A rich heterogeneity analysis suggests that negative selection into childbearing may explain the health effects and that cash transfers may increase birth weight for low-income families.
Keywords: H40; H75; I50; J13; J16; J18; 330; pro-natalist policies; cash transfer; fertility; infant health; sex ratio at birth; son preference